Subjetividad política presente en mujeres trans pertenecientes a grupos de performance en Bogotá D.C. (2018)
The present research presents elements of the construction of political subjectivity in four trans women from the city of Bogotá from artistic performance. One of the central approaches is how the body becomes a signifier of resistance to sex-gender identity system. Addressing approaches from social psychology, so An approach to the experiences of transgender people is proposed from gender studies, taking into account the sociopolitical development of transgender women in Colombia through the conversational interview as a data collection technique and that the results allow us to recognize from three categories the development of a felt subjectivity in an environment social movement away from legal activism, which allows us to identify the shortcomings that as a social state of law and as a society normalize the discrimination of an emerging identity.